Comparison of CT-measured angles of pelvic limbs without patellar luxation of six canine breeds - Brühschwein, Andreas; Burg-Personnaz, Juliette; Zöllner, Martin; Reese, Sven; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2023)
Introduction Dogs with medial patellar luxation can be affected by pelvic limb deformities whose corrective osteotomies and associated biomechanical rebalancing might provide higher success rates than standard surgical procedures limited to the stifle joint. In bilaterally affected canine patients, comparison with the contralateral normal limb is impossible. Reference values are useful for orthopedic decision-making. Inconsistency of published reference values might depend on methodology or canine breed. We hypothesized that canine pelvic limb alignment is breed-specific. Methods CT scans of 42 pelvic limbs of dog breeds predisposed for medial patellar luxation, with an orthotopic patellar position and stability were studied. Several angleswere measured with an open-source 3D Slicer plugin using vector calculations. The breeds were compared with a general linear model with a Bonferonni adjustment using SPSS. Results Chihuahuas, Pomeranians, Jack Russel Terriers, Pugs, French Bulldogs, Maltese were examined. In the order of the listed breeds, the angles were as follows: 28.3°±10.7°, 20.1°±2.9°, 35.4°±6.9°, 32.8°±3.0°, 19.0°±7.1°, 26.6°±5.3° for the antetorsion, 5.3°±1.8°, 2.8°±2.8°, 8°±4.4°, 3.8 °±3.1°, 4.7°±3.3°, 2.3°±3.3° for the femoral varus, of −5.5°±6.2°, 1.1°±4.1°, −5.2°±9.5°, 6.1°±8.0°, −0.1°±5.9°, −9.2°±4.7° for the tibial torsion, 2.0°±2.9°, 2.1°±2.7°, 6.4°±6.8°, 0.0°±5.7°, 3.0°±5.8°, 8.8°±8.6° for the tibial valgus, 1.2°±10.4°, 1.8°±3.4°, −1.7°±4.9°, −1.7°±9.4°, 5.1°±8.8°, −0.2°±8.6° for the femorotibial rotation and −3.4°±2.2°, 1.1°±4.1°, −2.8°±3.4°, −5.2°±4.0°, −2.1°±4.4°, −5.4°±3.7° for the tibiotalar rotation. There were significant differences between breeds in femoral torsion, femoral varus, and tibial torsion angles, but no significant differences in tibial valgus, femorotibial, and tibiotalar rotation angles. Discussion Our hypothesis is therefore partially correct. Our results are limited to small dogs prone to medial patellar luxation and might not be generalized. To establish robust reference values larger case numbers and more breeds should be evaluated. In conclusion, canine pelvic limb alignment reference values for small dogs with a predisposition for medial patellar luxation should be considered breed-specific.